Anti-inflammatory effects of the extracts from Ardisia silvestris Pitard leaves in experiment - Thanh, Mai Phuong; Dung, Ho My; Tuan, Le Anh; Huong, Nguyen Thuc Thu; Ngoc, Tran Thi Hong; Giang, Le Thi Le; Minh, Phan Hong (Tạp chí Nghiên cứu Y học, 2025)
This research aimed to explore the anti-inflammatory effects of n-hexane, ethyl acetate (EtOAc), and n-butanol extracts from the leaves of Ardisia silvestris Pitard, both in vitro and in vivo, specifically focusing on the EtOAc extract. The in vitro assessment of anti-inflammatory activity involved measuring the inhibition of nitric oxide (NO) production in LPS-stimulated RAW 264.7 macrophage cells. The findings revealed that the EtOAc extract exhibited the highest potency, with an IC50 value of 52.10 ± 2.07 µg/mL, effectively inhibiting NO production without causing cellular damage. In vivo, the EtOAc extract’s anti-inflammatory properties were evaluated using carrageenan-induced paw edema in rats and the cotton pellet-induced granuloma test in mice. At both tested dosages, the EtOAc extract significantly reduced paw edema induced by carrageenan in rats. Additionally, it effectively inhibited exudate and granuloma formation following cotton pellet implantation at both doses, indicating its anti-inflammatory activity during the subacute phase of inflammation. Overall, these results strongly suggest that the ethyl acetate extract of Ardisia silvestris Pitard possesses significant anti-inflammatory properties and may be beneficial in traditionally treating various inflammatory conditions.